Symbolic Interaction of Jamasan Kentongan Ritual in Pesanggrahan Village Batu City - Ghufron Ghufron; Dewi Dewi Chamidah; M. Rofik Fitrotulloh (Dialogia, 2021)
The cultural potential in Batu city is no less interesting than other regions in Java. One of the tradition cultural from Batu city is the Jamasan Kentongan ritual. This event is held on the anniversary of the Pesanggrahan Village Batu City. It aims to maintain and care for the ancestral culture. This research used a qualitative descriptive method. This research used the form of literature studies and interviews to collect the data. The theory that used in this study is theory cultural anthropology. The research results are a) Description about Procedures of process Jamasan Kentongan in Pesanggrahan village Batu city which have two procession, namely preliminary procession and ceremonial procession; b) the symbolic meaning of the tradition of jamasan kentongan is the umbo rampe that used in the jamasan ritual; c) The existence of patterns of religious and cultural dialectics in the Jamasan ritual from Pesanggrahan village Batu city.